Do the Effects of Resveratrol on Thermogenic and Oxidative Capacities in IBAT and Skeletal Muscle Depend on Feeding Conditions? - Milton-Laskibar, Iñaki (Nutrients, 2018)
The aim of this study was to compare the effects of mild energy restriction and resveratrol on thermogenic and oxidative capacity in interscapular brown adipose tissue (IBAT) and in skeletal muscle. Rats were fed a high-fat high-sucrose diet for six weeks, and divided into four experimental groups fed a standard diet: a control group, a resveratrol-treated group, an energy-restricted group and an energy-restricted group treated with resveratrol. Weights of IBAT, gastrocnemius muscle and fat depots were measured. Activities of carnitine palmitoyltransferase (CPT) and citrate synthase (CS), protein levels of sirtuin (SIRT1 and 3), uncoupling proteins (UCP1 and 3), glucose transporter (GLUT4), mitochondrial transcription factor (TFAM), nuclear respiratory factor (NRF1), peroxisome proliferator-activated receptor (PPARα) and AMP activated protein kinase (AMPK) and peroxisome proliferator-activated receptor gamma coactivator (PGC1α) activation were measured. No changes in IBAT and gastrocnemius weights were found. Energy-restriction, but not resveratrol, decreased the weights of adipose depots. In IBAT, resveratrol enhanced thermogenesis activating the SIRT1/PGC1α/PPARα axis. Resveratrol also induced fatty acid oxidation and glucose uptake. These effects were similar when resveratrol was combined with energy restriction. In the case of gastrocnemius muscle, the effects were not as clear as in the case of IBAT. In this tissue, resveratrol increased oxidative capacity. The combination of resveratrol and energy restriction seemingly did not improve the effects induced by the polyphenol alone.